Learning Topic Representation for SMT with Neural Networks - Cui, Lei; Zhang, Dongdong; Liu, Shujie; Liu, Shujie; Chen, Qiming; Li, Mu; Zhou, Ming; Yang, Muyun (ACL 2014, 2014)
Statistical Machine Translation (SMT) usually utilizes contextual information to disambiguate translation candidates. However, it is often limited to contexts within sentence boundaries, hence broader topical information cannot be leveraged. In this paper, we propose a novel approach to learning topic representation for parallel data using a neural network architecture, where abundant topical contexts are embedded via topic relevant monolingual data. By associating each translation rule with the topic representation, topic relevant rules are selected according to the distributional similarity with the source text during SMT decoding. Experimental results show that our method significantly improves translation accuracy in the NIST Chinese-to-English translation task compared to a state-of-the-art baseline.